2011
DOI: 10.1091/mbc.e10-11-0871
|View full text |Cite
|
Sign up to set email alerts
|

Deconstructing the ßcatenin destruction complex: mechanistic roles for the tumor suppressor APC in regulating Wnt signaling

Abstract: APC is a key tumor suppressor and Wnt signaling regulator, but its mechanism of action remains mysterious. We combined parallel assays in Drosophila and cultured human colon cancer cell lines to test hypotheses regarding APC function and to develop novel hypotheses, using mutants altering its structure in specific ways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
234
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(255 citation statements)
references
References 58 publications
(121 reference statements)
21
234
0
Order By: Relevance
“…Peifer and colleagues generated a Drosophila APC2 variant in which the SAMP repeats were deleted cleanly rather than by truncation, so that all b-cateninbinding sites were retained. This mutant APC was nonfunctional in animals, although b-catenin destruction and TCF signaling down-regulation were retained in SW480 cells (Roberts et al 2011). Curiously, Roberts et al 2011 found that APC2 lacking SAMP repeats colocalized with Axin, but the mutant APC2 did not coimmunoprecipitate with Axin, suggesting a weak and indirect interaction.…”
Section: The Role Of Apc In B-catenin Destructionmentioning
confidence: 99%
See 4 more Smart Citations
“…Peifer and colleagues generated a Drosophila APC2 variant in which the SAMP repeats were deleted cleanly rather than by truncation, so that all b-cateninbinding sites were retained. This mutant APC was nonfunctional in animals, although b-catenin destruction and TCF signaling down-regulation were retained in SW480 cells (Roberts et al 2011). Curiously, Roberts et al 2011 found that APC2 lacking SAMP repeats colocalized with Axin, but the mutant APC2 did not coimmunoprecipitate with Axin, suggesting a weak and indirect interaction.…”
Section: The Role Of Apc In B-catenin Destructionmentioning
confidence: 99%
“…This mutant APC was nonfunctional in animals, although b-catenin destruction and TCF signaling down-regulation were retained in SW480 cells (Roberts et al 2011). Curiously, Roberts et al 2011 found that APC2 lacking SAMP repeats colocalized with Axin, but the mutant APC2 did not coimmunoprecipitate with Axin, suggesting a weak and indirect interaction. It is possible that bcatenin itself bridged Axin and the mutant APC2, because it can interact with Axin and the APC 15-mer or nonphosphorylated 20-mer repeats simultaneously (Ha et al 2004).…”
Section: The Role Of Apc In B-catenin Destructionmentioning
confidence: 99%
See 3 more Smart Citations